2018
DOI: 10.1038/s41419-018-0536-7
|View full text |Cite|
|
Sign up to set email alerts
|

BRD7 inhibits the Warburg effect and tumor progression through inactivation of HIF1α/LDHA axis in breast cancer

Abstract: The bromodomain-containing protein 7 (BRD7) was first identified as a tumor suppressor in nasopharyngeal carcinoma and has critical roles in cancer development and progression. However, the regulatory roles and mechanisms of BRD7 in cancer metabolism are still unknown. In this study, we demonstrated that BRD7 was lowly expressed in breast cancer tissues and was identified as a poor prognostic factor in breast cancer. Meanwhile, BRD7 could suppress cell proliferation, initiate cell apoptosis and reduce aerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…A previous study showed that poly-ubiquitinated HIF1A was upregulated in BRD7-overexpressing MCF-7 breast cancer cells, indicating that BRD7 promotes the degradation of HIF1A in an ubiquitination-dependent manner in breast cancer. 30 Similarly, according to our data, HIF1A mRNA expression was upregulated, possibly revealing why BRD7 mRNA was highly expressed.…”
Section: Expression Of Genes Associated With the Warburg Effectsupporting
confidence: 75%
“…A previous study showed that poly-ubiquitinated HIF1A was upregulated in BRD7-overexpressing MCF-7 breast cancer cells, indicating that BRD7 promotes the degradation of HIF1A in an ubiquitination-dependent manner in breast cancer. 30 Similarly, according to our data, HIF1A mRNA expression was upregulated, possibly revealing why BRD7 mRNA was highly expressed.…”
Section: Expression Of Genes Associated With the Warburg Effectsupporting
confidence: 75%
“…Considering that p53 is a transcription factor, we then investigated whether p53 regulates the promoter activity of LDHA. As we have previously constructed a luciferase vector containing the LDHA potential promoter region (pLuc‐LDHA), we then transfected pLuc‐LDHA alone or cotransfected the p53 expression plasmid and pLuc‐LDHA into HEK293 and MCF7 cells and then detected the effect of p53 on the activity of the LDHA potential promoter using dual luciferase assays. As expected, ectopic expression of p53 greatly decreased the luciferase activity of the LDHA promoter in both MCF7 and HEK293 cells (Figure C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Many oncogenic proteins and tumor suppressors may regulate carcinogenesis through their regulatory roles in bioenergetics and metabolic pathways . p53 represses the expression of several glycolytic enzymes in an indirect or direct way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIFA is nuclear and constitutively expressed, whereas HIFB is cytoplasmic and controlled by oxygen-dependent enzymes. Several studies have indicated that HIF1A activity in various tumors is associated with poor prognosis through the regulation of angiogenesis, invasion, or metastasis [38][39][40]. In addition to HIF1A, HIF2A has been found to be strongly expressed in tumor-associated macrophages [41] and renal cell carcinoma [42], indicating the important roles of HIF1A and HIF2A in tumor progression.…”
Section: Discussionmentioning
confidence: 99%